International survey among orthopaedic trauma surgeons: Lack of a definition of fracture-related infection. Issue 3 (March 2018) - Morgenstern, M.; Moriarty, T.F.; Kuehl, R.; Richards, R.G.; McNally, M.A.; Verhofstad, M.H.J.; Borens, O.; Zalavras, C.; Raschke, M.; Kates, S.L.; Metsemakers, W.J.
Abstract: Introduction: Fracture-related infection (FRI) is one of the most challenging musculoskeletal complications in orthopaedic-trauma surgery. Although the orthopaedic community has developed and adopted a consensus definition of prosthetic joint infections (PJI), it still remains unclear how the trauma surgery community defines FRI in daily clinical practice or in performing clinical research studies. The central aim of this study was to survey the opinions of a global network of trauma surgeons on the definitions and criteria they routinely use, and their opinion on the need for a unified definition of FRI. The secondary aims were to survey their opinion on the utility of currently used definitions that may be at least partially applicable for FRI, and finally their opinion on the important clinical parameters that should be considered as diagnostic criteria for FRI. Methods: An 11-item questionnaire was developed to cover the above-mentioned aims. The questionnaire was administered by SurveyMonkey and was sent via blast email to all registered users of AO Trauma (Davos, Switzerland). Results: Out of the 26'563 recipients who opened the email, 2'327 (8.8%) completed the questionnaire. Nearly 90% of respondents agreed that a consensus-derived definition for FRI is required and 66% of the surgeons also agreed that PJI and FRI are not equal with respect to diagnosis, treatment and outcome. Furthermore, "positive cultures from microbiology testing", "elevation of CRP", "purulent drainage" and "local clinical signs of infection" were voted the most important diagnostic parameters for FRI. Conclusion: This international survey infers the need for a consensus definition of FRI and provides insight into the clinical parameters seen by an international community of trauma surgeons as being critical for defining FRI.